Urban response: an exploration of architectural systems modulated through mediums of digital sound and music - Lepore, Raffaella (My University, 2011)
URBAN RESONANCE explores the connections between architectural design and the multifaceted conceptual links to the idea of resonance in sound. This comparison is made in respect to the fact that a building is somewhat required to resonate with its urban context as well as to orchestrate the resonance relating to systems of people, built form and program, within itself. In using the concept of resonance, it is seen that these three systems, although separately definable, work together in one architectural environment – influencing each other in some way whether beneficial or not. I have chosen these three components of architectural design in response to Johannesburg’s urban and social context, and will explore their integration through celebrating their interstitial spaces of influence and resonance with each other. I seek to allow this idea in design, to produce new meaningful social encounters brought about by the exploration of cross-programming in a building coupled with an architectural response that enforces these social ideas. In the framework of Johannesburg, the question is not necessarily what the systems are but maybe rather how they can be unified and brought together in a building design. Sound is one of the least substantially manipulated and considered parts of building design, yet its relationship to inhabitants and their social connections to each other and space is powerful enough to allow people to perceive their surroundings solely through the things that they hear. URBAN RESONANCE is the explicit exploration of collective social ‘being’ in a building that uses sound and music to unify its programmatic and physical design within the context of Braamfontein, Johannesburg. Keywords:
Keywords: Resonant systems Sound and architecture Architectural systems Social encounters